2015
DOI: 10.1016/j.btre.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A simple and highly efficient Agrobacterium-mediated transformation protocol for Setaria viridis

Abstract: The production and use of sugarcane in Brazil is very important for bioenergy production and is recognized as one of the most efficient in the world. In our laboratory, Setaria viridis is being tested as a model plant for sugarcane. S. viridis has biological attributes (rapid life cycle, small genome, diploid, short stature and simple growth requirements) that make it suitable for use as a model system. We report a highly efficient protocol for Agrobacterium-mediated genetic transformation of S. viridis. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 9 publications
0
31
1
2
Order By: Relevance
“…Additional modifications of the Agrobacterium -mediated transformation methodology of S. viridis A10.1 were also reported by a second group (Martins et al, 2015b). Martins et al (2015b) followed similar methodology as reported by Van Eck et al (2017).…”
Section: Agrobacterium Tumefaciens- Mediated Transformation Of Maturementioning
confidence: 88%
See 3 more Smart Citations
“…Additional modifications of the Agrobacterium -mediated transformation methodology of S. viridis A10.1 were also reported by a second group (Martins et al, 2015b). Martins et al (2015b) followed similar methodology as reported by Van Eck et al (2017).…”
Section: Agrobacterium Tumefaciens- Mediated Transformation Of Maturementioning
confidence: 88%
“…In addition to the hpt selectable marker gene, vectors used for the development of the S. viridis transformation methodology also contained the beta-glucuronidase (GUS) and green fluorescent protein (GFP) reporter genes (Martins et al, 2015b; Van Eck and Swartwood, 2015). …”
Section: Agrobacterium Tumefaciens- Mediated Transformation Of Maturementioning
confidence: 99%
See 2 more Smart Citations
“…It is a short, fast-growing, C4 metabolism plant, with its draft genome sequence recently available, making it suitable model plant for genetic and genomics studies12. Moreover, S. viridis is highly responsive to Agrobacterium tumefaciens -mediated genetic transformation, with a well-established transformation protocols13 and more recently, spike-dipping methods have also been proposed34. S. viridis could be used as a model plant for food and bioenergy grasses presenting C4 metabolism such as maize, sorghum, sugarcane and switchgrass.…”
mentioning
confidence: 99%